Peningkatan Kapasitas Manajemen dalam Penilaian Kesehatan Keuangan Koperasi Konsumen Syariah Pegawai Negeri - Heri Faisal Harahap; Vicka Pramudya Putra; Roni Afrizal; Arnayulis Arnayulis; Veronice Azzukhruf Ariliusra (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
Cooperative health serves as a primary indicator of business credibility; however, the Koperasi Konsumen Syariah Pegawai Negeri Politeknik Pertanian Negeri Payakumbuh (KKSPN-PPNP) encounters significant obstacles in conducting systematic assessments due to limitations in human resource competence and the persistence of semi-manual reporting systems. The absence of such measurable evaluations negatively impacts the cooperative's internal accountability and its external bargaining position. This community service initiative aims to enhance the board's managerial capacity in independently compiling health assessment documents, in strict adherence to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and SMEs Number 06/PER/DEP.6/IV/2016. Employing a Participatory Action Research (PAR) approach, the program was implemented through a structured framework comprising socialization, classical training, and intensive mentoring to thoroughly analyze the seven vital aspects of health assessment. The results indicate a significant improvement in the administrators' technical understanding regarding financial ratio analysis and the implementation of early risk mitigation strategies. The primary output of this program is the generation of a valid Cooperative Health Assessment Report, which functions as an instrument of transparency during the Annual Members' Meeting (RAT) and serves as a strategic prerequisite for accessing banking financing. This achievement establishes a foundation for cooperative governance that is increasingly adaptive, accountable, and competitive.